Togo : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Joint Staff Advisory Note on the Poverty Reduction Strategy Paper for Togo, discusses that the new Strategy for Boosting Growth and Promoting Employment (SCAPE) presents the overarching reference framework for the Government's development agenda and reflects the authorities' aspiration to become, over the next 15-20 years, a middle income country, in which the rule of law and human rights are respected. The SCAPE draws upon the results of a nationally representative household survey (QUIBB). Being comprehensive, the SCAPE offers less in terms of prioritization. In light of persistent capacity constraints and limited financing, it would have been advantageous if the SCAPE had presented a clearer perspective on the Government's role in the development process, if a more focused growth and social development strategy had been articulated, and if SCAPE's implementation mechanisms had been closer aligned with existing decision-making mechanisms. The IMF staff suggests that the SCAPE's analysis could be supplemented with additional analyses on the impact of SCAPE policies on poverty, inequality and (rural) employment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet